PENERAPAN GAME MAZE CHASE UNTUK MENINGKATKAN ASPEK KOGNITIF SISWA KELAS V PADA MATA PELAJARAN IPA TENTANG SISTEM PENCERNAAN MANUSIA DI MI NAGARAKASIH 1 KOTA TASIKMALAYA - Nurmatin, Suci; Upi Nispi Sabani (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2025)
This study was motivated by the low cognitive performance of fifth-grade students in science subjects, particularly on the topic of the human digestive system. Pretest results showed that students’ understanding was still low, with an average score of 56.82 and only 36.4% meeting the minimum mastery criteria, indicating that previous learning methods were less effective. The aim of this study was to examine the implementation and improvement of students' cognitive aspects after applying an interactive learning medium based on the Maze Chase game. The research used a quantitative approach with a pre-experimental one-group pretest-posttest design. The subjects were 22 fifth-grade students at MI Nagarakasih 1 Kota Tasikmalaya. The research instruments included observation sheets and multiple-choice cognitive tests developed based on Bloom’s Taxonomy (C1–C4). The data were analyzed using descriptive and inferential statistics, including N-Gain and paired sample t-tests with the assistance of SPSS 26 software. The results showed an increase in the average score from 56.82 (pretest) to 83.41 (posttest), with the percentage of students achieving mastery increasing from 36.4% to 81.8%. The average N-Gain score was 0.65, categorized as moderate to high, and the t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. Therefore, the use of Maze Chase is proven effective in enhancing students' cognitive performance and is considered a suitable learning medium for science education in elementary schools, especially on the topic of the human digestive system.